Popularion biology of abdominant fish species of the Santa Bárbara river, a tributary of the Nova Avanhandava reservoir (low Tietê river, São Paulo State, Brazil) - Vidotto-Magnoni, Ana Paula [UNESP]; Carvalho, Edmir Daniel [UNESP] (Universidade Estadual de Maringa, 2009)
The aim of this study is to characterize some population biology parameters of P. squamosissimus, A. altiparanae and S. maculatus, the dominant fish species of the Santa Bárbara river, a tributary of the Nova Avanhandava reservoir, low Tietê river. Fish samplings were performed monthly between September/2002 and August/2003, using gill nets with different mesh sizes. Females of all species have larger standard lengths than males (Mann-Whitney, p < 0.0001), and are more frequent in superior size classes (Kolmogorov-Smirnov, p < 0.0001). All populations presented isometric growth, but differences between males and females were observed. Only P. squamosissimus presented a gender ratio different from 1:1, with a higher proportion of males (1:2, X2, p < 0.05). The onset of gonadal maturation occurs at 15 cm in P. squamosissimus, 9 cm in S. maculatus and at 8.9 cm in A. altiparanae. In all species populations, the adults predominate over juveniles. The allometric condition factor (K) of P. squamosissimus and S. maculatus presented higher values in the periods from March-May and June-August, and A. altiparanae in the period from March-May (Kruskal-Wallis, p < 0.05). These results indicate that the populations successfully exploit the lentic environment, and present life cycle tactics adapted to their particular means of environment occupation.
Keywords: Astyanax altiparanae; Plagioscion squamosissimus; Population biology; Reservoir; Serrasalmus maculatus; Tietê river; Age distribution; Body height; Brazil; Controlled study; Female; Fish; Gonad development; Growth rate; Life cycle assessment; Male; Nonhuman; Population abundance; Population biology; Reservoir; River; Seasonal variation; Sex difference; Sex ratio; Species comparison; Species dominance; Water supply; Serrasalmus